The Callus of Phaseolus coccineus and Glycine max Biotransform Flavanones into the Corresponding Flavones - Monika Dymarska; Tomasz Janeczko; Edyta Kostrzewa-Susłow (Molecules, 2020)
In vitro plant cultures are gaining in industrial importance, especially as biocatalysts and as sources of secondary metabolites used in pharmacy. The idea that guided us in our research was to evaluate the biocatalytic potential of newly obtained callus tissue towards flavonoid compounds. In this publication, we describe new ways of using callus cultures in the biotransformations. In the first method, the callus cultures grown on a solid medium are transferred to the water, the reaction medium into which the substrate is introduced. In the second method, biotransformation is carried out on a solid medium by growing callus cultures. In the course of the research, we have shown that the callus obtained from Phaseolus coccineus and Glycine max is capable of converting flavanone, 5-methoxyflavanone and 6-methoxyflavanone into the corresponding flavones.